The Influence of Expertise, Audit Experience, Ethics, and Knowledge of Accounting and Auditing on the Accuracy of Audit Opinion Giving - Jihan Rahmawati; Dian Puji Puspita Sari; Nur Fitriana (Journal of Social Research, 2026)
Background: The accuracy of audit opinions is a critical element in maintaining the credibility of financial reporting and ensuring stakeholder trust. Various individual auditor characteristics such as expertise, audit experience, ethics, and accounting and auditing knowledge are assumed to influence the quality and accuracy of audit judgments. Objective: This study aims to determine the effect of expertise, audit experience, ethics, and accounting and auditing knowledge on the accuracy of audit opinions. Methods: This research applies a quantitative approach using primary data collected through questionnaires. The sample consisted of 61 auditors selected using the census method. Data were analyzed using descriptive statistics and multiple linear regression analysis. Results: The findings show that expertise does not significantly affect the accuracy of audit opinions. However, audit experience, ethics, and accounting and auditing knowledge have significant effects on the accuracy of audit opinions. Conclusion: The study concludes that audit experience, ethics, and accounting and auditing knowledge play important roles in improving the accuracy of audit opinions, while expertise alone is not sufficient to influence audit opinion accuracy. These findings highlight the importance of practical experience and ethical competence in strengthening audit quality.